THE DIRECTION OF FISHERY DEVELOPMENT IN INDONESIA, AND SOME NOTES ON FUNCTIONAL CHANGE OF PEKALONGAN HARBOUR FROM PUBLIC TO FISHERY HARBOUR, 1940-1980 - Sutejo K. Widodo (JOURNAL OF COASTAL DEVELOPMENT, 2000)
The Java sea has abundant supplies of fish M various species In the past, along the northern coatl of Java, there were several fish landing centers along the northern coast af Java. The Report of the Commissie van ( Commission of) Mindere Welvaart { report] in 1905 mentioned that the existence of these places was related to the ecology of sea sources. Up to the end cf the colonial government, the policy in fish consumption was based on the import of fish, especially dried and salted fish. The policy was maintained up to the Indonesian era in 1961. Afterwards, fish needs was filled through a policy of sefsrwiciency. This policy was able to support efforts in fishery development. Pekalongan harbour was built in 1852 and opened in 1859 cu a public harbour for export-import Since the earlv Twentieth Century, the function of Pekalongan harbour has declined as a result ofthe modernization of Semarang harbour. In 1974, the Pekalongan harbour was the first harbour to be converted from a trade harbour into a special fishery harbour. The functional change and the development ofthe harbour in the following years are related to the great changes in fishery policy and developments in other areas of 1%.. Pekalongan harbour was tranjormed into one of the most interesting fishery harbours in Java because it has several advantageous factors such as topography, safety guarantee, local sources for informed capital,conducive policy of the central government, geography, and local availability ofmiddle level technology.